What a paediatrician should know about congenital clubfoot - Daniela Dibello; Valentina Di Carlo; Giulia Colin; Egidio Barbi; Anna M. C. Galimberti (BMC, 2020)
Abstract Clubfoot is the most frequent congenital malformation of the foot, affecting more than 1-2 subjects per 1.000 newborns. Without appropriate treatment, a child with congenital clubfoot will never be able to walk physiologically with a dramatic impact on the quality of life. In the last decades, different corrective solutions have been proposed, and there is rising scientific evidence that the Ponseti non-invasive method is safe and effective in the treatment of the clubfoot. So, what should a general paediatrician know about this condition and what should he concretely do in the suspect of a congenital clubfoot?